PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP PENGUNGKAPAN PENGENDALIAN INTERNAL - Alfita Rakhmayani; Faisal Faisal (KRISNA: Kumpulan Riset Akuntansi, 2019)
Internal control system is a key aspect in providing the completeness and reliable information. The adequately of internal control system disclosure may help stakeholders in assessing the quality of corporate’s internal control system and also can reduce asymmetric information. This study examines the effect of audit committee characteristics on internal control disclosure. The sample consists of 100 public companies with the largest market capitalization in 2016. The statistical regression analysis was performed to test the hypotheses. The results show that number of audit committee meetings has a positive effect on the internal control disclosure. However, this study failed to provide evidence that number and education background of audit committee contribute in enhancing the extent of internal control disclosure. This finding suggests that audit committee play a role in reducing asymmetric information through the broader internal control disclosure.